Gambaran Perilaku Self Injury pada Remaja di Wilayah Sleman Yogyakarta - Islamarida, Rista; Tirtana, Arif; Devianto, Aan (Universitas Tribhuwana Tunggadewi, 2023)
Adolescence is the transitional age from childhood to adulthood, and there are many changes during this period. The change that occurs is not only physical but also psychological. A lot of the stresses in the lives of teenagers make them look for ways to solve the problem. A teenager who can cope with problems well will go through adolescence well. However, there are some adolescents who are unable to cope with the problem, which will cause negative effects such as emotional instability. Because of these unstable emotions, teenagers use inappropriate ways to deal with their problems, such as self-harm behavior. This study aims to paint a picture of self-injury in adolescents. The study used descriptive analytical methods using the Self-Harm Inventory questionnaire for data collection. The research was carried out in the district of Sleman among teenagers aged 14–20 who were spread across 14 districts in Sleman. The total number of respondents was 1,362, taken using the cluster sampling technique. The results of the study showed that the majority of adolescents had low self-harm behaviors, with a percentage of 66.6%. However, attention should still be paid to adolescents who have high self-harm behaviors (a percentage of 3.4%). So further research is still needed to find out the various factors that affect self-injury behavior in adolescents.